Influence of nano particles on the performance parameters of lube oil – a review. (3rd November 2021) - Singh, Anoop Pratap; Dwivedi, Ravi Kumar; Suhane, Amit
Abstract: This review focuses on the effect of nanoparticles in lubricating oil performance. The impact of chemical composition, particle size, and nanoparticle shape is evaluated on lubricants' lubricating capabilities. The effects of base oils and surfactants, and dispensers are also covered. This review demonstrates a comparative study of nanoparticles based on the maximum reduction in friction and wears values and the obtained minimum coefficient of friction (COF). The above three performance parameters collectively provide a better understanding of the role of nanoparticles in lubricating oil performance.